Comparative study of short term and long term protocols for progesterone based estrus synchronization in ewes during breeding season - MALIK, A A; FAZILI, M R; KHATUN, A; ATHAR, H; NAIKOO, M; KHAN, H M; SHAH, R A; SHABIR, M (The Indian Journal of Animal Sciences, 2022)
The study was designed to compare the effect of length of progesterone treatment (6 d vs 10 d vs 14 d) on synchronization efficiency and fertility response in multiparous ewes. The crossbred ewes (30) were equally allotted to three groups designated as short (6 days), medium (10 days) and long-term (14 days) treatment. All the ewes were injected PGF2α 250 μg, intramuscularly 24 h before sponge removal. After the sponge removal ewes were kept with breeding rams for tupping upto 72 h. Although the onset of estrus was more precise in short and long term groups, however overall estrus response rate was highest in short treatment group (90%) followed by long treatment group (70%) and medium treatment group (60%). The pregnancy rates were non-significantly higher for short and medium treatment groups than long treatment group. The progesterone values in pregnant ewes, decreased significantly from day pre-treatment to day 0 followed by significant increase from day 0 to day 10, 17 and 35. In conclusion, short term (6 d) intravaginal progesterone treatment may replace the traditional long term treatment (14 d) for induction of estrous during breeding season. However, the results should be validated in larger number of animals before recommending the protocol.